The association between DXA‐derived body fat measures and breast cancer risk among postmenopausal women in the Women's Health Initiative. (25th December 2019) - Arthur, Rhonda S.; Xue, Xiaonan; Kamensky, Victor; Chlebowski, Rowan T.; Simon, Michael; Luo, Juhua; Shadyab, Aladdin H.; Neuhouser, Marian L.; Banack, Hailey; Ho, Gloria Y. F.; Lane, Dorothy S.; Pan, Kathy; et al.
Abstract: Background: Most studies demonstrating an association between excess adiposity and postmenopausal breast cancer have used anthropometric measures, particularly body mass index (BMI). However, more direct body fat measures may more accurately determine the relationship between body fat distribution and breast cancer risk. Methods: Cox proportional hazards regression models were created to examine the associations of dual‐energy x‐ray absorptiometry (DXA) body fat measures (at baseline and during follow‐up) with breast cancer risk among 10 931 postmenopausal women from the Women's Health Initiative cohort. A total of 639 incident invasive breast cancer cases (including 484 estrogen receptor positive (ER+) cases) were ascertained after a median follow‐up of 15.0 years. Results: Excess whole body fat mass and trunk fat mass were positively associated with risk invasive breast cancer risk. These associations persisted even after additional adjustment for standard anthropometric measures. In time‐dependent analyses, we observed that both whole body fat mass and trunk fat mass, in the highest versus lowest category, were associated with a doubling of risk of invasive breast cancer overall (HR: 2.17; 95% CI: 1.54‐3.05 and 2.20; 1.55‐3.14, respectively) and of ER+ breast cancer (2.05; 1.37‐3.05 and 2.03; 1.34‐3.07, respectively). The remaining DXA measures were also positively associated with breast cancer risk in baseline and time‐dependent analyses. Conclusion: These findings suggest that DXA‐derived body fat measures are positively associated with breast cancer risk after adjustment for BMI and other conventional breast cancer risk factors. Abstract : Our study demonstrated that DXA‐derived body fat measures were positively associated with breast cancer risk after adjustment for BMI and other conventional breast cancer risk factors. These findings suggest that DXA‐derived measures of overall and central adiposity may explain invasive breast cancer risk beyond that of BMI and other risk factors.